1997
DOI: 10.1021/bi962741b
|View full text |Cite
|
Sign up to set email alerts
|

Localization of an Effective Fibrin β-Chain Polymerization Site:  Implications for the Polymerization Mechanism

Abstract: To examine whether fibrin N-terminal Aalpha 17-23 and Bbeta 15-25 may contain high-affinity polymerization sites, GPRVVER and GHRPLDKKREE analogs were prepared, and their abilities to inhibit fibrin monomers from repolymerizing were compared in turbidity and clottability assays. Within Aalpha 17-23, GPR is the most active site (IC30 of 0.95-1.36 mM). Its extension into GPRVVER (IC30 of 1.75-2.3 mM) reduced activity. Within Bbeta 15-25, acyl-DKKREE (IC30 of 0.30-0.53 mM) can account for GHRPLDKKREE activity (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…It is reasonable to conclude that any or all of the chain heterogeneities contribute to these differences. We favor an important contribution from the N-terminal residues of the β-chain (48)(49)(50). It is known that β15-18 participates in fibrin polymerization, so loss of these residues in X 1 and X 2 could have a dramatic effect.…”
Section: Discussionmentioning
confidence: 78%
“…It is reasonable to conclude that any or all of the chain heterogeneities contribute to these differences. We favor an important contribution from the N-terminal residues of the β-chain (48)(49)(50). It is known that β15-18 participates in fibrin polymerization, so loss of these residues in X 1 and X 2 could have a dramatic effect.…”
Section: Discussionmentioning
confidence: 78%
“…Prior work revealed the reduced clot turbidity, modified clot ultra-structure and altered mechanical properties of fibrinogen Osaka VI, which contains a short 12 amino acid extension on the β-chain, and thereby indicated that the β-chain terminus was involved in fibrin polymerization (23). Other observations showed that a 37-amino acid peptide equivalent to the sequence γ374-411 of the γ-chain bound inhibited the polymerization of fibrin oligomers and decreased the maximal turbidity of the fibrin clots (10)(11)(12). Calorimetry, fluorescence, HPLC and size exclusion techniques showed that a 32-amino acid peptide equivalent to the γ374-405 could non-covalently attach to fibrinogen fragment D3.…”
Section: Discussionmentioning
confidence: 99%
“…Calorimetry, fluorescence, HPLC and size exclusion techniques showed that a 32-amino acid peptide equivalent to the γ374-405 could non-covalently attach to fibrinogen fragment D3. In free form, wild and truncated versions of the γ374-405 peptide tended to self-associate and spontaneously formed oligomers (10)(11)(12)(13). Combined, these reports suggested that a large portion of the C-termini of both β and γ chains of normal fibrin(ogen) were involved in the assembling the monomers into a clot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations